2021
DOI: 10.1051/e3sconf/202125402023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the silicon compounds effect on disease resistance and productivity of spring barley with a decrease in pesticide load in the south of Russia

Abstract: In a small-plot field experiment, the effect of different forms of silicon compounds (tetraethoxysilane (TES) and sodium silicate) and processing methods (seeds and plants) on disease incidence and productivity of spring barley varieties was studied and the effect of diseases on productivity was evaluated. It was found that the use of silicon-containing compounds separately and in a mixture with a reduced consumption rate of fungicide led to a decrease in the infestation of barley with root rot and leaf spots.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In our previous field of studies, it was found that the use of silicon compounds such as tetraethoxysilane (TES) and sodium silicate in tank mixtures with pesticides increased the effectiveness of the latter and allowed reducing the application rates of fungicides by 50% and insecticides by 20% without reducing the effectiveness of protective agents [16,17]. The decrease in application rates will also affect the indicator of the relative ecological and toxicological danger of use: for fungicides, it will decrease by two times, and for insecticides-by 20%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous field of studies, it was found that the use of silicon compounds such as tetraethoxysilane (TES) and sodium silicate in tank mixtures with pesticides increased the effectiveness of the latter and allowed reducing the application rates of fungicides by 50% and insecticides by 20% without reducing the effectiveness of protective agents [16,17]. The decrease in application rates will also affect the indicator of the relative ecological and toxicological danger of use: for fungicides, it will decrease by two times, and for insecticides-by 20%.…”
Section: Resultsmentioning
confidence: 99%
“…In Russia, this is the state catalog of pesticides and agrochemicals approved for use on the territory of the Russian Federation [15]. Therefore, technologies that allow reducing the application rates of pesticides without loss of effectiveness against pests are promising; for example, the use of pesticides with silicon compounds [16,17]. Currently, information technologies are increasingly being used in agro-ecological monitoring [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Additive agents include various adhesives and film-forming agents; some of them have their own biological activity. The studies have shown that TES and sodium silicate have contributed to increasing the plants' resistance to adverse factors: diseases and pests, moisture deficiency (drought) [12,13,14]. The use of selenium compounds is also promising; those increase both the productivity of plants and their resistance to stress [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…The use of selenium compounds is also promising; those increase both the productivity of plants and their resistance to stress [15,16]. Combined use of silicon compounds with pesticides allowed to reduce the consumption rates of fungicides by 50%, insecticides -by 20% without reducing the effectiveness of protective equipment [12,13,14].…”
Section: Resultsmentioning
confidence: 99%
“…[7][8] One of the aspects of the modern agro-industrial complex aimed at reducing the influence of abiotic environmental factors on agricultural crops is the improvement of plant nutrition systems through the use of various means to reduce the effect of oxidative stress on plants caused by these factors. [9][10][11]…”
Section: Introductionmentioning
confidence: 99%